2018
DOI: 10.1002/cjoc.201700726
|View full text |Cite
|
Sign up to set email alerts
|

Rh‐catalyzed Transient Directing Group Promoted C—H Amidation of Benzaldehydes Utilizing Dioxazolones

Abstract: Transition‐metal catalyzed C—H functionalization of benzaldehydes is of great interest in organic synthesis. Herein, we developed a transient directing group assisted amidation of benzaldehydes catalyzed by rhodium catalyst. With the employment of 10 mol% of 4‐trifluoromethyl aniline, the in situ generated imine groups as the directing group efficiently enable this transformation. By using this protocol, a wide range of benzaldehydes were efficiently converted into the corresponding N‐(2‐formylphenyl)benzamide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 114 publications
0
19
0
6
Order By: Relevance
“…Yu, Zhang, and co‐workers and Chen, He, and co‐workers independently developed Ir‐catalyzed ortho ‐amidation reactions with organic azides using electron‐poor anilines ( L14 and L15 ) as transient ligands (Scheme b, c) . In addition, using 4‐trifluoromethylaniline ( L16 ) as the transient ligand, Jiao and co‐workers found that dioxazolone could be used as an amide source for the ortho ‐amidation of benzaldehydes in decent yields via decarboxylation and migratory insertion steps (Scheme d) . In 2017, Zhang and co‐workers reported the ruthenium catalyzed ortho ‐alkylation of benzaldehydes with maleimides by using 2‐methyl‐3‐(trifluoromethyl) aniline ( L17 ) as a transient ligand (Scheme e).…”
Section: Reversible Covalent Bonding For Transition Metal‐catalyzed Cmentioning
confidence: 99%
“…Yu, Zhang, and co‐workers and Chen, He, and co‐workers independently developed Ir‐catalyzed ortho ‐amidation reactions with organic azides using electron‐poor anilines ( L14 and L15 ) as transient ligands (Scheme b, c) . In addition, using 4‐trifluoromethylaniline ( L16 ) as the transient ligand, Jiao and co‐workers found that dioxazolone could be used as an amide source for the ortho ‐amidation of benzaldehydes in decent yields via decarboxylation and migratory insertion steps (Scheme d) . In 2017, Zhang and co‐workers reported the ruthenium catalyzed ortho ‐alkylation of benzaldehydes with maleimides by using 2‐methyl‐3‐(trifluoromethyl) aniline ( L17 ) as a transient ligand (Scheme e).…”
Section: Reversible Covalent Bonding For Transition Metal‐catalyzed Cmentioning
confidence: 99%
“…Sie erwiesen sich als nützlich fürD iversifizierungen in einem späten Stadium. [57][58][59] Füre inen effizienten Umsatz ist die Art des Liganden entscheidend. Verschiedene heterocyclische Substrate 4.1.…”
Section: Angewandte Chemieunclassified
“…Verschiedene heterocyclische Substrate 4.1. [58,59] Durch die Einführung einer dirigierenden Gruppe mit einem nukleophilen oder elektrophilen Charakter wird nach einer vorausgehenden C-H-Amidierung eine anschließende intramolekulare Cyclisierung ermçglicht, die die Bildung von bicyclischen Verbindungen fçrdert (Schema 20). Seit der wegweisenden Arbeit von Sauer und Mayer 1968 [56] hat die auf diesen Heterocyclen basierende decarboxylierende Tr ansformation viel Interesse geweckt.…”
Section: Angewandte Chemieunclassified
See 2 more Smart Citations